Redefining Ownership and Originality in the Age of AI: A Legal and Ethical Review - Vebritha, Silvy (Sinergi International Journal of Law, 2024)
The proliferation of artificial intelligence (AI) in the creative sector presents novel legal and ethical challenges to existing intellectual property (IP) frameworks. This study aims to explore how the growing role of AI in producing original works affects current IP laws, particularly in determining ownership and originality. Using a narrative review method, the research synthesizes literature sourced from Scopus, Google Scholar, and PubMed, filtered through strategic keyword combinations and strict inclusion criteria. It examines interdisciplinary findings covering legal theory, policy, ethics, and empirical case studies from multiple jurisdictions. The results indicate that while human involvement in algorithm design remains central to IP claims, the autonomous creative contributions of AI necessitate reformulation of legal concepts such as authorship and originality. Moreover, the study reveals significant jurisdictional disparities in legal treatment of AI-generated works, with systemic issues such as lack of international harmonization and outdated legislation contributing to legal uncertainty. Ethical concerns around dataset use and the risks of unauthorized reproduction also emerge as central themes. The discussion proposes solutions including sui generis IP models, blockchain verification systems, and cross-border policy frameworks to address these issues. The study concludes by emphasizing the urgency of coordinated legal innovation and ethical governance to ensure fair and effective IP protection in the AI era.